A statistical analysis of an innovative concept of Trombe Wall by experimental tests. (15th December 2022) - Szyszka, Jerzy; Bevilaqua, Piero; Bruno, Roberto
Abstract: The Trombe Wall (TW) is one of the most effective passive heating systems that can be used in cold climates to provide solar gains to indoor environments. This study introduces an analyses of the effect of some boundary conditions on an innovative solution of the TW, named Thermo-Diode Trombe Wall (TDTW), which was designed to ensure significant thermal insulation for the building envelope and, at the same time, allows for exploiting solar gains rationally. Laboratory tests carried out in a climatic chamber setting proper indoor and outdoor temperature conditions allowed for calculating the thermal efficiency with reference to the absorbed solar radiation, simulated by a specific apparatus that permitted to vary the intensity and duration of the thermal energy provided to the TDTW absorber. An experimental plan was defined according to the Design of Experiment (DoE) theory, setting 16 tests conducted varying the external air temperature, the absorbed energy and the time duration. The analysis allowed for obtaining the correlation between the thermal efficiency and the selected boundary conditions. Results showed how the thermal efficiency in the tests performed ranged between 21.58% and 30.30%. A statistical analysis allowed for determining the equation of the response surface that provides the efficiency as a function of the independent variables. Employing the nonlinear estimation method, results confirmed the adequacy of such an equation with a coefficient of determination R 2 = 0.802 and a critical significance level p = 0.00016, much lower than the assumed 5% threshold. Highlights: An innovative highly insulated Trombe Wall was tested in laboratory conditions. An experimental plan was designed according to the Design of Experiment theory. The thermal efficiency of the TW was evaluated from experimental tests. A statistical analysis was conducted to determine relations between the efficiency and outdoor conditions.